THE STATE OF UZBEK SCIENTIFIC LINGUISTICS - Rimboyeva Nazira Rashid kizi (Bright Mind Publishing, 2025)
Uzbek scientific linguistics has developed significantly in recent decades, incorporating both traditional linguistic approaches and modern interdisciplinary methodologies. This article explores the current state of linguistic research in Uzbekistan, focusing on historical developments, contemporary trends, and future directions. Special attention is given to the impact of digital technologies, corpus linguistics, and sociolinguistic studies on Uzbek linguistics. The study also highlights challenges such as standardization, integration with global linguistic research, and the need for enhanced methodological approaches.
Keywords: Uzbek linguistics, language research, corpus linguistics, sociolinguistics, linguistic methodology, digital linguistics.